As cores na natureza: uma proposta para o ensino de óptica ondulatória - Silva, César Augusto Vassalo (2018)
The study of colors is usually only done in arts classes in elementary school, without taking into consideration aspects related to light, that could be discussed in physics classes. In order to teach about this theme, we developed a didactic sequence which adresses this issue with other concepts of wave optics. For this purpose, during the teaching-learning process, there were problematizations, present in the activity scripts delivered to high school second year students, in a public school, located in a small town of Minas Gerais. We aimed to investigate their alternative conceptions about colors, as well as to whet the curiosity to seek explanations about the studied phenomena. The results show that few students thought about aspects related to vision to explain phenomena involving colors in nature, most of which referred only to lightobject interaction as an explanation for color perception.